Γ-MnOOH-graphene nanocomposite as promising anode material for Li-ion capacitors. (March 2022) - Varghese, Shibu P.; Babu, Binson; Surendran, Vishnu; Damien, Dijo; Antony, Rosy; Shaijumon, Manikoth M.
Highlights: Large-scale synthesis of γ-MnOOH-graphene through simple hydrothermal route. γ-MnOOH- graphene exhibits remarkable electrochemical properties. Studied as efficient anode material for Li-ion battery and Li-ion capacitor. The LIC exhibits excellent capacitive retention (∼80%) upon 8500 cycles. Abstract: Developing environmentally benign electrode materials with faster Li-ion kinetics is an essential requirement for high-performance Li-based energy storage devices. Here we report the large-scale synthesis of γ-MnOOH-graphene (γ-MnOOH-rGO) nanocomposite, through a simple hydrothermal route, for their application as potential anode material in Li-ion batteries. As-synthesized nanocomposite with the γ-MnOOH nanorods uniformly anchored on the graphene sheets exhibits enhanced electrochemical performance and achieves a very high specific capacity of ∼435 mAh g −1 at a current density of 1.0 A g −1 . Detailed electrochemical studies reveal faster Li-ion kinetics in γ-MnOOH-rGO nanocomposite electrode, dominated by non-diffusion controlled processes (∼ 80% at 1.0 mV s −1 ). Further, the full-cell Li-ion capacitor fabricated with γ-MnOOH-rGO nanocomposite as the anode and activated carbon as the cathode exhibits a maximum energy density of ∼51 Wh kg −1 and a maximum power density of ∼ 6.3 kW kg −1, with excellent capacity retention of more than ∼87% upon 8500 cycles. The present work thus demonstrates γ-MnOOH-graphene nanocomposite as promising anode material for advanced Li-ion batteries and high power Li-ion capacitors. Graphical abstract: Image, graphical abstract